KONTRIBUSI IKLIM KERJA DAN MOTIVASI KERJA TERHADAP KREATIFITAS PAMONG BELAJAR SANGGAR KEGIATAN BELAJAR (SKB) DI WILAYAH LUAK NAN TIGO PROVINSI SUMATERA BARAT - Riswandi Riswandi (IAIN Batusangkar, 2018)
This research is motivated by the invisibility of creativity yet tutors in Sanggar Kegiatan Belajar (SKB). This study aims to reveal about the contribution of the working climate and work motivation on creativity tutors Sanggar Kegiatan Belajar (SKB) in the region Badger Luak Nan TigoWest Sumatra Province. Based on the problems and goals to be achieved, this study used a quantitative method that aims to examine the relationship between the three variables above are correlational against a population of 42 tutors with a sample size of 28 people. Sample selection is done through four stages with the steps as follows: (1) Identify strata of the population, (2) Calculate the proportion of strata, (3) determine the sample size, and (4) determining the subject of research. To do research instruments (1) Measurement Scale, (2) Preparation of Instrument, and (3) Test Instruments. Data collected by distributing a questionnaire in the form of questionnaires to tutors selected as the study sample. The research data were processed and analyzed by using the Correlation Technique and Multiple Linear Regression Technique. Data analysis was performed with the aid of a computer program SPSS version 18.0 For Windows, to perform requirements analysis, and hypothesis testing. Results of the analysis showed that (1) contribute to the climate of creativity tutors, (2) contribute to the creative work motivation tutors, and (3) work climate and work motivation together also contribute to the creativity tutors.